Work addiction, emotional dysregulation, addictive eating, and physical health among full-time employees in the United States - Catherine So-Kum Tang (Frontiers in Psychology)
Background and aimsThis study explored the psychological mechanisms linking work addiction to poor physical health among full-time employees. The proposed serial multiple mediation model suggests that work addiction depletes employees’ ability to regulate emotions, leading to addictive eating as a coping mechanism, which creates a vicious cycle that severely impairs physical health.MethodsThe sample consisted of 1,233 full-time employees (aged 25–65 years) in the United States, who completed an online survey assessing work addiction, emotion regulation deficits, addictive eating, and physical functioning.ResultsAmong all participants, the rates were 13.1% for food addiction, 9.7% for work addiction, and 3.5% for co-occurrence of food and work addiction. Compared to men, women reported a higher rate of food addiction, but the rates of work addiction were similar for both genders. The proposed model was tested using bootstrapping analysis, and the findings supported the serial multiple mediation model. The indirect effect of work addiction on poor physical health, mediated first by emotional dysregulation and then by addictive eating, was significant. Although the direct effect of work addiction on physical health was reduced when accounting for the mediators, it remained significant. The results also indicated that gender did not significantly moderate these relationships, showing consistent findings across men and women.DiscussionWork and eating addictions are common among full-time employees. Findings underscore the complex pathway through which work addiction exacerbates physical health problems via emotional and behavioral mechanisms.ConclusionWork addiction impacts physical health both directly and indirectly, and is associated with emotional dysregulation and addictive eating. Implementing wellness programs that address emotional reactivity and provide nutrition education is essential to mitigate the negative health impacts of work addiction.